Digital education as a new pedagogical paradigm - Tuguz, F.A. (Вестник Майкопского государственного технологического университета, 2023)
The society is characterized by the expansion of digital services into all spheres of human life, including education. The digital technology sector plays a leading role in the development of a digital society. The introduction of digital services into education at all its levels is supported by government initiatives as a promising guideline for the transformation of the entire society, taking into account global practices. The research problem is: what are the mechanisms of digital education as a new pedagogical paradigm? The purpose of the research is to substantiate the features of digital education as a new pedagogical paradigm and a component of state educational policy. The research methods are data analysis of Internet sources, scientific works, generalization, systematization. The research results: new educational opportunities through the use of digital resources have been substantiated; the main features of digital education have been identified; the prospects for digital education as an innovative model have been outlined. Key findings: the introduction of digital education into a university environment has been considered in two contexts: as a necessary content of education and as a means of teaching; the main features of digital education focus on consumer preferences, organization of rational user interaction, algorithmized interaction of its users, remote work with information resources, network interaction, etc.; infection for various consumer groups; the ability to operate on different means and compatibility with other applications; the prospects for digital education are the construction of an ergonomic communicative environment of an educational institution, the possession of digital competencies by all subjects of education; motivation of scientific and pedagogical personnel to work in a new educational environment, updating academic disciplines, etc.